An Efficient Algorithm for Recognition of Human Actions - Yaser Daanial Khan; Nabeel Sabir Khan; Shoaib Farooq; Adnan Abid; Sher Afzal Khan; Farooq Ahmad; M. Khalid Mahmood (The Scientific World Journal)
Recognition of human actions is an emerging need. Various researchers have endeavored to provide a solution to this problem. Some of the current state-of-the-art solutions are either inaccurate or computationally intensive while others require human intervention. In this paper a sufficiently accurate while computationally inexpensive solution is provided for the same problem. Image moments which are translation, rotation, and scale invariant are computed for a frame. A dynamic neural network is used to identify the patterns within the stream of image moments and hence recognize actions. Experiments show that the proposed model performs better than other competitive models.